Assisted Suicide in Parkinsonian Disorders - Nuebling, Georg S.; Butzhammer, Elisabeth; Lorenzl, Stefan (Frontiers in Neurology, 2021)
Background: Due to the high prevalence of suicidal ideation in Parkinson’s Disease (PD) and exploratory data indicating a similar prevalence in atypical Parkinsonian disorders (APD), we sought to determine the frequency of assisted suicide (AS) as well as factors driving these decisions in PD and APD. Methods: Retrospective chart analysis (2006-2012) at a Swiss Right-to-Die organization. Patients with PD and APD who completed AS were analyzed concerning disease state, symptom burden, medication and social factors. Results: We identified 72 patients (PD=34, PSP=17, MSA=17, CBS=4; 7.2% of all AS cases), originating mainly from Germany (41.7%), Great Britain (29.2%) and the US (8.6%). Predominant symptoms at the time of application were immobility (PD/APD: 91%/97%), helplessness (63%/70%), pain (69%/19%), dysarthria (25%/32%) and dysphagia (19%/59%). APD patients generally showed a higher symptom burden and a higher frequency of diagnosed depression (28.9%/8.8%). While most patients with diagnosed depression received antidepressants (80%), other symptoms such as pain (59%) were treated less consistently. Of note, time from diagnosis to application differed greatly between PD (8.5±6.8 years) and APD (1.5±1.3 years, p<0.0001). Conclusions: In our analysis, Parkinsonian disorders appeared to be overrepresented as a cause of AS considering the prevalence of these diseases. The observation that assisted suicide is sought early after initial diagnosis in APD implies the need for early comprehensive psychological support of these patients and their relatives.